Strategic Approaches to Enhancing Teachers Competence in Artificial Intelligence for the Transformation of 21-st Century Education - Sayni Nasrah; Sri Milfayetty; Arif Rahman; Muthmainnah Muthmainnah (AIBPM Publisher, 2025)
The development of information and communication technology, particularly Artificial Intelligence (AI), has impacted various sectors, including education. This study aims to explore strategies for enhancing teachers' competencies in mastering AI at junior high schools through educational and training programs. The main focus of this research is to understand teachers' experiences and perceptions regarding the effectiveness of AI training in improving their professional competencies for 21st-century learning. This research employs a qualitative approach with a case study design at public junior high schools in Lhokseumawe. Data collection methods include in-depth interviews, classroom observations, and the analysis of relevant documents. The findings indicate that the majority of teachers who participated in AI training reported improvements in their professional competencies, particularly in using technology for automated assessments and providing instant feedback. However, the main challenges faced by teachers include the lack of advanced training and inadequate infrastructure. School management support and collaboration among teachers were identified as crucial factors in the successful implementation of AI in the classroom.This study suggests the need for more applicable advanced training, enhanced technological infrastructure, and continuous guidance to support a more effective integration of AI into the learning process.